MODEL PENINGKATAN PEMAHAMAN DAN PENGAMALAN AJARAN AGAMA SANTRI MANULA PADA MAJLIS TA’LIM RAUDLATUL JANNAH DI DUKUH MATSARI DESA PESANGGRAHAN KECAMATAN BATU KOTA BATU - Mamduh 'Amali; Maskuri Bakri; Mohammad Afifullah (Vicratina : Jurnal Ilmiah Keagamaan, 2020)
Education is a conscious and systematic effort that is carried out not only to humanize humanity but so that humans realize their position as Khalifatullah fil Ard, which in turn will be able to improve themselves into pious, faithful and knowledgeable people and be able to increase understanding and practice religious teachings. If this can be owned and applied in everyday life, then it is not impossible if we have a high degree of degree. So in this case the Islamic ummah is in need of amalia science and scientific charity. So from here the importance of understanding and practice of religious teachings by knowing the model of increasing understanding and practice of religious teachings of senior students in Majlis Ta'lim Raudlatul Jannah Hamlet Matsari Pesanggrahan Village Batu District Batu City.